Perancangan Model Spasial Kawasan Permukiman Perkotaan Berbasis Cellular Automata Di Kabupaten Minahasa Selatan - Tarumingkeng, Francis Andreas; Kapantow, Gene H.M.; Pakasi, Sandra Engelin (AGRI-SOSIOEKONOMI, 2023)
The purpose of this research is to design a spatial model of urban settlement areas using the Cellular Automata approach in South Minahasa Regency. The research location is located in a sub-district in South Minahasa Regency which has a delineation of urban settlement areas namely Tumpaan, Tareran, Amurang Timur, Amurang, Amurang Barat, Tenga and Sinonsayang Districts, covering an area of ​​656.6 Km2. Primary data collection methods are: Field observation and distribution of questionnaires to academics, government and local communities. Secondary data collection methods, namely: literature review and data request survey. The method of analysis is quantitative analysis using AHP and spatial analysis based on Cellular Automata. The results of the research show that the direction of modeling starts towards the east and south of the research location. Urban residential land in the research location experienced a growth of 4.19% from the previous year in 2014 covering an area of ​​11.96 Km2 increasing by 15.26 Km2 to 27.22 Km2 in 2034. The modeling results also show that in the 2014-2019 range is the range in which growth the highest settlement that occurred was 5.7%. The development of settlements resulted in the conversion of several land uses, namely alang-alang land and mixed gardens. Urban settlements in Tareran District are settlements that experience greater growth among settlements in other districts with a percentage reaching 9.1%.